Improved strength-plasticity in a lean duplex stainless steel through multiple cold rolling and short-term annealing - Jiale Zhang; Yumeng Zhang; Laizhu Jiang; Xiangyong Xiao; Qingmao Kong; Xiaodong Wang; Kolan Madhav Reddy (Journal of Materials Research and Technology)
In this study, a lean duplex stainless steel (DSS) 2001 with a bimodal ferrite structure and fine austenite phase was obtained by innovative multiple cold rolling and short-term incomplete annealing. The yield strength of this bimodal structural stainless steel was significantly increased from 436.2 MPa to 640.2 MPa, while maintaining a high tensile strength of 929 MPa and elongation of about 52 %. Microstructural characterization reveals that combining multiple cold rolling with incomplete annealing promotes ferrite grain refinement and induces the formation of a bimodal grain structure through partial recrystallization. Additionally, staged annealing promotes nitrogen retention and subsequent enrichment in the austenite phase, thereby enhancing mechanical stability and inhibiting the occurrence of transformation induced plasticity (TRIP) effect at early deformation stage. This study offers valuable insights for optimizing alloy heat treatment and rolling process selection for such DSS.